Volatility spillover between Gold Spot & future market in India: An Experiment with Multi commodity Exchange - Saha, A; Chakraborty, S; Mitra, G (International Journal of Computer Sciences and Engineering, 2025)
In economics spillover effects i are economic events in one context that occur because something else in a seemingly unrelated context. When more information about someone generates more information about people related to her and that information helps to eliminate asymmetries in information, then the spillover effects are positive. Spillover from disequilibrium in one market may influence effective demand in other market. In the present initiative we venture to investigate whether the volatility in the spot price have a spill over effect on futures price or vice-versa. As India is one of the largest market markets for gold and growing affluence is driving growth in demand, we focus on Gold spot and future market. We have collected daily data from MCX for the period from 1 st April 2008 to 31 st March 2018. Our basic objective is to investigate the spill over effect of spot market volatility on futures prices volatility or vice versa. In order to complete our experiment we have done descriptive statistics, unit root test, ARCH test, GARCH test on our sample data. Having completed our experiments and obtaining results on measurement of price volatility in both segments of the market we take further initiatives to run exponential GARCH (Nelson and Cao, 1991) and threshold GARCH (Zakoian,1994) models. The reasons behind our model selection are in the pursuit of usefulness in asset pricing Exponential GARCH (EGARCH). Threshold GARCH (TGARCH) is different from Jagannathan-Runkel GARCH (1993) only in one parameter. In TGARCH model specification is on conditional standard deviation instead of conditional variance. Our TGARCH has captured asymmetric effects of positive and negative shocks of the gold futures market in India. We are confident that our research contributes towards greater understanding of (i) direction of spill over effect and (ii) asset pricing and leverage effects in the gold futures market. The results of our experiment